Caesarean Section in Confirmed COVID-19 Patient at Nepalgunj Medical College: Case Report - Sinha, Kavita; Kushwaha, Amrendra; Adhikari, Homnath (Journal of Nepalgunj Medical College, 2020)
An outbreak of novel coronavirus pneumonia occurred worldwide since December 2019, which had been named COVID-19 subsequently. It is extremely transmissive that infection in pregnant women were unavoidable. The delivery process will produce large amount of contaminated media, leaving a challenge for medical personnel to ensure both the safety of the mother and infant and good self-protection. Here, we report a 27 year woman had reverse transcription polymerase chain reaction-confirmed COVID-19 at 37 weeks 2 days of gestation. An emergency caesarean section at 38 weeks 2 days of gestation under spinal anaesthesia was performed for oligohydramnios with scar tenderness with strict protection for all personnel.